An Interaction between Employee Psychological Capital, Perceived Organizational Fit, and Work Well-Being on Organizational Commitment: An Empirical Study on E-Commerce Industry in Indonesia - Nangoy, Rizal; Hamsal, Muhammad (Journal of Strategic and Global Studies, 2018)
The joining of the Millennial generation with their different characteristics and values in the workforce has brought new challenges to human capital management. However, research related to employee well-being and organizational commitment of the Millennial generation is still difficult to find in Indonesia. This study aims to investigate the role of psychological capital and perceived organizational fit to employee well-being and organizational commitment of the Millennial employees in e-commerce industry in Indonesia. Data were collected through a survey of 288 Millennial employees who work in e-commerce industry in Jakarta. We found that employee well-being and organizational commitment are positively associated with both psychological capital and organizational fit, while employee well-being also mediates the relationship between psychological capital and perceived organizational fit toward organizational commitment. The results contribute to better understanding of attitude of the Millennial generation and specifically to the predictors of employee well-being and commitment at work, especially in the e-commerce industry.